Information sharing as strategic behaviour: the role of information display, social motivation and time pressure. Issue 6 (3rd June 2017) - Bălău, Nicoleta; Utz, Sonja
ABSTRACT: In today's knowledge economy, given the increasing number of online collaborative platforms, it is even more important to understand and manage the sharing of information. Although it is widely accepted that technological design affects how people use a platform, it is a real challenge to constantly stimulate information sharing (IS), also because individuals often behave strategically, that is, share relatively unimportant information, but keep the important private information for themselves. This research aims to understand how people's motivations and aspects of communication technology interact to affect IS. Specifically, we expand the view of IS as strategic behaviour by investigating (1) how social motivation (prosocial vs. pro-self) and time pressure (high vs. low), interactively, impact strategic IS and (2) how technological features (push- vs. pull-information display) can increase the sharing of private information. Across two experiments, we found that push-information displays increase the sharing of private information. This held especially for individuals with a prosocial motivation. Additionally, we found that actual and not perceived time pressure impacts (private) IS. Implications for technological design choices and knowledge management are discussed.